A novel gaseous chlorine dioxide generating method utilizing carbon dioxide and moisture respired from tomato for Salmonella inactivation. (July 2018) - Zhou, Siyuan; Hu, Changying; Zhao, Guohua; Liu, LinShu; Sheen, Shiowshuh; Yam, Kit L.
Abstract: Chlorine dioxide (ClO2 ) is an antimicrobial compound used in fresh produce sanitation. Compared to its aqueous form, gaseous ClO2 has an enhanced antimicrobial effect. This research proposed a novel generating method of ClO2(g) that utilized carbon dioxide and moisture naturally released from tomato during respiration to react with sodium chlorite for ClO2(g) generation. The results showed that the generated ClO2(g) not only effectively reduced the surface-inoculated Salmonella by 4 log CFU/fruit to an undetectable level (<5 CFU/fruit) within 24 h, but also did not impact the surface color and firmness of the fruits within the entire storage period (144 h) at 22 °C. The effects of NaClO2 amount (0.05, 0.1 and 0.2 g), CO2 concentration (7.5 and 15%), RH (45 and 95%), temperature (10, 22 and 35 °C) and pH (4, 5, 7 and 9) on the release of ClO2(g) were evaluated. The D and z values of Salmonella under different temperatures were obtained. A sachet system was successfully developed for the practical applications of this novel ClO2(g) generating method. Highlights: Proposed a novel method of ClO2(g) generation. Evaluated effects of many factors on ClO2(g) release. Obtained D and z values of Salmonella under different temperatures. Developed a sachet system for practical applications of the novel method.